Cyril of Alexandria speaks for God in his interpretation of the Holy Bible - Artemi, Eirini (Acta theologica, 2014)
Cyril of Alexandria is known more for his defence of Alexandrian Christology than for his accomplishments as an interpreter of the Old and New Testaments. Although the fathers were aware that the Old Testament’s idiom differed from that of the New Testament, they considered the Bible to be one book and that each part thereof complemented the other. Cyril emphasises that “[t]he entire Scripture is one book, and was spoken by the one Holy Spirit” (Isaiah PG 70, 656A).1 The unity of the Bible is based on Christ; without him, it is difficult to view Leviticus, Proverbs, Ezekiel, Mark’s gospel, the Acts of the Apostles or the first epistle of John as part of one Holy Book, the Bible.